Strategies for Covalent Labeling of Long RNAs. (17th June 2021) - Depmeier, Hannah; Hoffmann, Eva; Bornewasser, Lisa; Kath‐Schorr, Stephanie
Abstract: The introduction of chemical modifications into long RNA molecules at specific positions for visualization, biophysical investigations, diagnostic and therapeutic applications still remains challenging. In this review, we present recent approaches for covalent internal labeling of long RNAs. Topics included are the assembly of large modified RNAs via enzymatic ligation of short synthetic oligonucleotides and synthetic biology approaches preparing site‐specifically modified RNAs via in vitro transcription using an expanded genetic alphabet. Moreover, recent approaches to employ deoxyribozymes (DNAzymes) and ribozymes for RNA labeling and RNA methyltransferase based labeling strategies are presented. We discuss the potentials and limits of the individual methods, their applicability for RNAs with several hundred to thousands of nucleotides in length and indicate future directions in the field. Abstract : Decorating long RNAs : This review discusses currently available approaches for the introduction of reporter groups into large RNA molecules at internal positions in a site‐specific fashion to allow visualization, tracking and structural investigations on long RNAs.